Trinidad and Tobago : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Trinidad and Tobago. (IMF Staff Country Reports; Country Report ;, 2022)
Trinidad and Tobago faced unprecedented challenges in 2020-21. The combined effects of COVID-19 and energy production and price shocks pushed the economy further into recession. A decisive policy response helped contain the virus spread and protect lives and livelihoods. The fiscal position worsened due to significant tax revenues shortfalls, pushing public debt up. The vaccination pace accelerated recently, but vaccine hesitancy remains high, amid a potential new wave of infections.